Maternal mortality : report of meeting held at Friends' House. Euston Road on November 15, 1932 (London : Maternal Mortality Committee)
1932-11 1932 1930s 36 pages working at that subject all day and every day, and it is, I think, very difficult for those who are in authority to fully realise the enormous importance which the women of this country attach to this problem of Maternal Mortality and Morbidity. Compared to the casualties that take place in the industrial world, the casualties are extremely high. We have all had brought before our notice during the last week very painfully the dangers that attend the lives of those who are going down the mines to dig coal. I remember that about six years ago I made a rough calculation for some purpose of my own of the comparison between the death-rate of coal miners and the maternal death-rate, and I came to this conclusion that when a coal miner's wife gave birth to a baby she ran rather more than twice as much risk of death as her husband ran going down the coal mine every day for a year, judging by the respective number of deaths in childbirth compared to the number of confinements and the death-rate in coal-mining. But the point I want to speak about in the minute or two available for me is rather the question of Maternal Morbidity. While we are very grateful for the valuable inquiry that we have had into Maternal Mortality, and while we all intend to do our utmost to see that the Report is carried out, I should like to see a big and far-reaching inquiry into the rate of Maternal Morbidity, in short, into the causes that make the mother so liable to succumb when she reaches the confinement. I think we have all felt very alarmed at the evidence which has come before us of the unhealthy condition of married women. When last summer we were discussing in Parliament the problems of the Insurance Bill those of us who were taking part in the discussion all realised, though there was a hesitation about actually putting it into words, a belief in the air that the terribly high rate of sickness among married women as compared with any other class of insured person was due to the fault of married women, that they gave way too easily. I am not going to discuss here whether there is any malingering among married women or not, but rather I would say, "How much do we know, and what grounds have we got for our opinion as to the health of married women as a class?" There again some six years ago I wanted to collect what statistics were available — for a purpose of my own — illustrating that point, and I got the help of a very able woman economist from the School of Economics. I asked her to get for me any figures she could as to the health of married women, especially when they are not employed. Her report was rather like the famous report on snakes in Ireland, which ran : "There are no snakes in Ireland." It was comparable because she said that she could find almost no statistics which did bear upon the health of the married women. (18) 292/824/1/45